Pengaruh Paparan Asap Rokok Elektrik terhadap Histologi Paru Mencit (Mus musculus L.) Strain Balb/c Jantan - Eva Tyas Utami; Bella Dwi Arifianti; Mahriani; Susantin Fajariyah (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Electric cigarette is a type of cigarette that change the liquid containing nicotine and other ingredients in the form of steam. This research aimed to identify the effect of exposure to e-cigarette smoke towards the thickness of bronchioles mucosa and the alveolar septa on male Balb'C mice (M. musculus). Methods: This research was an experimental design used 24 male divided into four groups, i.e., control dan three treatment groups. Treatment groups were given different volume of e-cigarettes liquid, i.e., 1 ml; 2 ml; and 4 ml. The exposure of e-cigarette was done in 4 weeks, respectively. Results: Electric cigarette exposure with different fluid volumes leads to an increase in the bronchioles mucosa's thickness and the alveoli septa. Increasing the volume of fluid used results in an increase in bronchioles mucosal thickness, but decreases the alveoli septa's thickness, resulting in destruction and dilatation of the alveoli. Conclusion: Exposure to e-cigarette smoke with a liquid volume of 1 ml affects the increase in the average thickness of the bronchial mucosa and alveoli septa. An increase in the average thickness of the bronchioles mucosa occurs along with increased fluid volume in exposure to e-cigarette smoke.